Geology and potential of rock slope failure using kinematic analysis method in Anabanua Village, Barru Regency, South Sulawesi - Nordin, Nur Haikal (2019)
This study was focused about geology and potential of rock slope failure using kinematic analysis method in Anabanua Village, Barru Regency in South Sulawesi. The objectives of this study are to produce the general geological map of study area on a scale 1:25,000 and to investigate the potential of rock slope failure using kinematic analysis method. Geological mapping method was used in studying the geology of study area to produce the geological map with the scale of 1:25,000. Geological map showed the distribution of the rock and its associated structural geology. The data that were analysed to produce the geological map was geomorphology, lithostratigraphy, structural geology and historical geology of study area. Rock samples were taken for petrography analysis to identify the type of rock in study area. The lithologies identified in the study area were limestone, tuff, volcanic breccia and trachyte intrusion. For the rock slope analysis, kinematic analysis method used to investigate the influence of structural geology towards the stability of the slopes. In the study area there were 4 slopes that have been identified to potentially occur rock slope failure that consist of trachyte rock slope and limestone rock slope Those rock slope formed as rock slope that cut through main road in Anabanua Village, known as Jalan Poros Barru-Soppeng which is very hazardous to the road users if slope failure occur. In kinematic analysis, orientation of discontinuity, its persistence and spacing between discontinuites were measured and analysed using stereonet software. The result gained in this research is the probability of failure, type of failure and direction of failure. The result shown that 2 of 4 rock slope were unstable and probably will fail due to the direction of the discontinuity were nearly parallel to the slope face which will cause sliding of the rock block.